Analisis Semiotika Saussure pada Tayangan Talkshow “Anda Sakit? Panggil Saja Sule, Dijamin Ketawa” - Zahratul Zahratul; Santri Mauliani; Nurul Warahma Purba; Nur Halimah; Bungsu Keumala Sari (Indo Publishing, 2026)
Humor is one of the forms of communication that plays an important role in entertainment media, particularly in comedy talk shows that rely on verbal interaction and language play. This study aims to analyze the construction of humor in the talk show Anda Sakit? Panggil Saja Sule, Dijamin Ketawa through Ferdinand de Saussure’s semiotic perspective. A descriptive qualitative approach was employed using semiotic analysis focusing on the relationship between signifier and signified. The data consisted of humorous utterances produced by Andre Taulany and Nunung in the selected talk show episode uploaded on YouTube. Data were collected through observation, documentation, and transcription techniques, and analyzed by identifying signifiers, signifieds, and the meanings generated from their relationship. The findings reveal that humor is constructed through several semiotic patterns, namely analogy, semantic deviation, hyperbole, ambiguity, and linguistic absurdity. These patterns demonstrate that the relationship between signifier and signified is intentionally manipulated to create incongruity and produce comedic effects. The study concludes that humor in the talk show is not merely a form of entertainment but also a process of meaning construction through linguistic signs. The findings contribute to the development of semiotic studies, particularly in understanding verbal humor in television and digital media..